The Application of Brand Authenticity in Increasing Brand Trust in Crafting Brand - Putri, Diva Amanda; Dirgantari, Puspo Dewi (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2024)
Brand authenticity has emerged as an important concept in branding and marketing research, representing the perception that a brand is genuine, reliable, and in line with its core values and identity, which can influence consumer purchasing decisions. This study aims to examine the application of brand authenticity in enhancing brand trust in the context of business brand crafting. The method used in this research is descriptive qualitative which allows an in-depth understanding of the role of brand authenticity on brand trust of one of the crafting businesses in Bandung, named Gift.in with direct interviews with business owners. the results show that the gift.in brand has not optimally implemented four important factors in building brand authenticity. These factors include consistency, transparency, value congruence and emotional connection.